2018
DOI: 10.1590/0034-7167-2017-0928
|View full text |Cite
|
Sign up to set email alerts
|

Teaching of infection control in undergraduate courses in health sciences: opinion of experts

Abstract: In order to cover the complexity of the elements that are interconnected for professional training, teaching must be based on pedagogical strategies that provoke reflection in students, encouraging them to develop critical thinking about their experiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
0
8
0
5
Order By: Relevance
“…A previous study suggests that to boost reflection and critical thinking of the student, IPC education should be emphasized before entering the fields of practical activities [17]. The findings of this study showed that nursing…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…A previous study suggests that to boost reflection and critical thinking of the student, IPC education should be emphasized before entering the fields of practical activities [17]. The findings of this study showed that nursing…”
Section: Discussionmentioning
confidence: 62%
“…Thus, it is difficult for clinician mentors to guide students in various clinical settings to guess what level of IPC education students are receiving [11]. Studies emphasized the need to teach IPC education to be an exclusively transversal subject in the curriculum of course in all its phases aiming to understand the amplitude and complexity of the subject by the student [17,26]. In order to explore IPC education in the undergraduate nursing curriculum, we tried to include focus group panels in different universities and different nursing major areas, and this attempt was the first attempt in Korean nursing education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of policies and guidelines does not necessarily ensure implementation in resource-limited settings. Introduction of structured curricula in medical and nursing education and in-house training of healthcare workers (HCWs) through workshops and CMEs will help in capacity building [32][33][34]. An area of opportunity lies in translation of international guidelines into simple local languages, which can be followed by groundlevel HCWs in their day-to-day practices.…”
Section: Ipc Education Training and Researchmentioning
confidence: 99%
“…Dentre as medidas mais utilizadas para promoção e educação em saúde, podemos citar os materiais impressos bastante utilizados para melhorar o conhecimento e a auto responsabilização do paciente frente à sua saúde. Estudos recomendam a utilização de materiais impressos para reforçar orientações verbais, sabe-se que esses materiais auxiliam nas possíveis dúvidas do paciente, contribuindo com informações seguras e atemporais na ausência de um profissional em saúde (1)(2)(3)(4)(5) .…”
Section: Introductionunclassified